Importance of Macroprudential Policy Implementation for Safeguarding Financial Stability - Milena Vučinić (Journal of Central Banking Theory and Practice, 2016)
The crisis pointed to the necessity for strong and stable financial system resistant to potential risks and shocks. Macroprudential policy is used to identify, monitor and asses systemic risks to financial stability. Therefore, it is very important to create effective and efficient macroprudential policy. To achieve this, it is crucial to create a strong institutional framework. This paper deals with the importance of macroprudential policy for financial system stability. The first part of the paper explains the macroprudential policy and its connection with other economic policies. The second part refers to the necessity of building strong institutional framework and the importance of providing clear responsibilities for macroprudential policy, as long as precise determination of responsibilities is very suggested and important for further functioning and policy implementation. Responsibilities for macroprudential policy and macroprudential supervision defers among countries.
Keywords: E52; E58; E61; E62; G18; 330; macroprudential policy; financial stability; economic policies; institutional framework.